Designing an optimal PID controller for a PV-connected Zeta converter using genetic algorithm - Hussain, Abadal-Salam T.; Taha, Faris Hassan; Fadhil, Hilal A.; Salih, Sinan Q.; Taha, Taha A. (Institute of Advanced Engineering and Science, 2024)
This paper suggests a way of fixing problems of voltage fluctuations and peak overshoot in a PV-connected Zeta converter system. The Zeta converter in the proposed approach is controlled using proportional integral derivative (PID) while a genetic algorithm (GA) calculates the PID coefficients based on the control mechanism. The performance of the designed system was analyzed in a MATLAB/Simulink environment. The analysis showed that the proposed system reduced the output voltage ripple and peak overshoot during transient conditions by providing feedback to the converter through the PID controller, this is a significant improvement when compared to the results found without a PID controller.